1992
DOI: 10.1364/ao.31.005712
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of kinoform structures for optical computing

Abstract: The fabrication of kinoform micro-optical elements for applications in optical computing is described. The elements are recorded as continuous microrelief structures by programmable laser beam writing in photoresist with a computer-controlled precision xy stage and a modulated, focused laser beam. Kinoform structures can be programmed to any desired profile that is required for reproducing complex, optimized structures that are found by computer design techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…8 (the nm shims were slightly different modulation amplitudes are due to smaller shims different measurement line positions). An atomic ;tructure.1 5 force microscope profile measurement of the central 140 [im x 140 Aim of the 400 pim x 400 jm unit cell is shown in Fig. 9.…”
Section: Diffraction Ordersmentioning
confidence: 99%
See 2 more Smart Citations
“…8 (the nm shims were slightly different modulation amplitudes are due to smaller shims different measurement line positions). An atomic ;tructure.1 5 force microscope profile measurement of the central 140 [im x 140 Aim of the 400 pim x 400 jm unit cell is shown in Fig. 9.…”
Section: Diffraction Ordersmentioning
confidence: 99%
“…4 They can be fabricated by laser-beam writing in photoresist by using a high-precision scanning system with tight control of the resist processing. 5 Once this technology has been established, it can be effectively used for the fabrication of a wide variety of phase DOE's and other micro-optical components; the writing procedure is a single-step process, so the main effort in fabricating new microstructures would be in the design and programming. The fabrication of replicas by embossing or casting from a metal shim enables large numbers of elements to be generated from a single recording.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work described was carried out at the Paul Scherrer Institute Zurich (PSIZ) using a laser writing system set-up in the early 1980s [9] and continuously improved in subsequent years [10,11,21. The technology developed enables a wide range of microoptical elements to be fabricated, including Fresnel microlenses and lens arrays, kinoform elements and general microrelief phase structures for a variety of applications in optical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Possessing a high diffraction efficiency, the kinoform optical elements are widely used for the beam splitting (fanout), beam shaping, and pattern or image generation [1,2] . The detailed description of the weighting iterative Fourier transform (WIFT) algorithm was given earlier [3] , where we also showed that it is most efficient for the synthesis of the kinoforms of binary objects.…”
mentioning
confidence: 99%